The role of outsourcing in driving global carbon emissions. Issue 2 (2nd April 2016) - Malik, Arunima; Lan, Jun
ABSTRACT: Globalisation has narrowed the gap between producers and consumers of goods and services. The linkages between international trade and carbon dioxide (CO2 ) emissions have started to be recognised, yet the extent of outsourcing of emissions across nations is unknown. Filling this gap in knowledge is critical for designing effective policy mechanisms for assigning responsibility for reductions in emissions. Here we present a structural decomposition analysis of global trends in outsourcing of emissions from 1990 to 2010 for 186 individual countries. To this end, we disaggregate total CO2 emissions for each country into contributions from the domestic economy and international trade. This allows us to unveil outsourcing trends for all nations confirming a world-wide shifting of emissions-intensive production across borders. We categorise nations into "outsourcers" – countries that outsource carbon-intensive production to so-called contractor nations. Our detailed assessment of the commodity content of global outsourcing flows reveals interesting insights about the trade of carbon-intensive commodities.